비강 내 호산구 수와 호산구 비율의 상관관계 및 진단의 유용성 - 윤규현; 김경훈; 윤종서; 김현희 (Allergy asthma & respiratory disease, 2020)
Purpose: Allergic rhinitis is the most common atopic disease and the most common chronic disease of children. Eosinophil count and percentage in nasal smear are useful for differential diagnosis of allergic rhinitis. The aim of this study is to investigate the correlation between nasal eosinophil count and percentage. Methods: Between January 2017 and August 2018, 221 children patients with a clinical history of rhinitis were tested at the outpatient respiratory and allergy unit of the Department of Pediatrics, School of Medicine, The Catholic University of Korea. Nasal secretion was collected by swabbing a children's nasal inferior turbinate 3–4 times with a cotton swab and then placed on to a glass slide. Later, the smear was stained by Giemsa stain. Results: This is the first study to assess the comparison of nasal eosinophil count and percent. There is a positive correlation between nasal eosinophil count and percent Y=1.02 X+2.82 (Y=Eosinophil count, X=Eosinophil percentage). To determine the usefulness of nasal eosinophil count and percentage in the diagnosis of allergic rhinitis, we analyzed receiver operating characteristic curves. The cutoff value of the nasal eosinophil count was 6.5/high-power field, and that of the nasal eosinophil ratio was 3% for the diagnosis of allergic rhinitis. Conclusion: In patients with suspected rhinitis, one of the values of nasal eosinophil count or percentage can be used in clinical practice. KCI Citation Count: 0